EFFECTIVE TECHNIQUES FOR DEVELOPING PHONETIC COMPETENCE IN ENGLISH CONVERSATION GROUPS - Namozova Dilnoza Berdimurotovna; Rashidova Munavvar Xaydarovna (TADQIQOTLAR.UZ, 2023)
Annotation: This article describes different motivating strategies of how to raise the interest of students to English language acquisition by organizing conversation groups and developing phonetic competence of students.